THE USE OF KAHOOT APPLICATION ON STUDENTS VOCABULARY MASTERY - Awaludin, Neilan Sabila (Journal of English Teaching and Linguistics Studies (JET Li), 2023)
The objectivity of this research is to know the effect of using Kahoot application on students vocabulary mastery. The research was conducted to the second grade of Junior High School. Quantitative approach with quasi-experimental method and chose only post-test design. The approach used in this research. There were 38 students in each class for class J as a control group and class K as experimental group.  The data were taken from post-test and were analyzed using t-test formula. According to the data calculation, the writer found that the average score of the experimental class is higher than the control class. Based on the statistical results of the t test, it was obtained that the significance value is 0.056 score with the significance value 0.05 (taken from the significance level 5%). It can be concluded that the use of Kahoot application has no effect on students' vocabulary mastery.Keywords: Application, Kahoot, Vocabulary Mastery.